Relación entre la tasa de desempleo con la tasa de empleo informal en la región Loreto, periodo 2013 – 2022 - Paredes Navarro, Diana Carolina (2025)
The present research aimed primarily to analyze the relationship between the unemployment rate and the informal employment rate in the Loreto region from 2013 to 2022. It is a quantitative study with variables that can be measured, employing a non-experimental design since the variables were not manipulated, a longitudinal design as data were collected over different periods, and a descriptive-correlational scope that describes the relationships between the unemployment rate and the informal employment rate. The following conclusions were reached: The general hypothesis, which states the direct relationship between the unemployment rate and informal employment in the Loreto region, is accepted. A Pearson correlation coefficient of 0.662108178 was calculated, which falls within the interval -1 ≤ r ≤ 1, and since the result is positive, it indicates that the line is ascending. Additionally, specific hypotheses 1 and 2 are accepted, which affirm that the unemployment and informal employment rates in the Loreto region were increasing; this was supported by the Shapiro-Wilk normality test, demonstrating the normality of the unemployment rate variable with a p-value of 0.377 > 0.05 and of the informal employment rate with a p-value of 0.963 > 0.05. Finally, specific hypothesis 3, which states that the level of correlation between the unemployment rate and the informal employment rate is excellent, is rejected since the coefficient of determination is 43.84%, indicating a minimal correlation.